Post traumatic stress disorder (PTSD): The psychological sequelae of abnormally invasive placenta (AIP) - Tol, ID; Yousif, M; Collins, SL (Elsevier, 2019)
Introduction Abnormally invasive placenta (AIP) is a rare pregnancy complication often resulting in postpartum haemorrhage (PPH) and emergency peripartum hysterectomy (EPH). The risk of developing post traumatic stress disorder (PTSD) following unexpectedly traumatic childbirth is known however there is no evidence regarding PTSD in AIP. This pilot study assesses the risk of PTSD for women with AIP compared to women having an uncomplicated caesarean delivery (CD) or unexpected PPH or EPH. Methods Retrospective case-controlled questionnaire study in a UK Tertiary obstetric unit. Women with AIP (Group-1) were matched by delivery date to control groups: Group-2, women with an uncomplicated CD; Group-3 women referred to a specialist clinic for suspected AIP, but had a normal placenta and uncomplicated CD; Group-4, women who had an unexpected EPH and/or severe (>3000 mls) PPH. 218 women were sent a validated PTSD screening questionnaire (Impacts of Events Scale-Revised [IES-R]). Results Likelihood of PTSD was recorded for 69 women who responded, revealing significantly higher PTSD scores for women with AIP compared to uncomplicated CD (P = 0.001). No significant difference was seen between AIP and EPH/PPH (P = 0.89). The number of women with scores high enough to indicate probable PTSD was significantly greater with AIP than uncomplicated CD group (P = 0.045). Discussion This study demonstrates that women antenatally diagnosed with AIP and anticipating a potentially traumatic delivery, are at significantly increased risk of developing PTSD. Improved awareness of the negative psychological impact of AIP may increase the number of women being identified and treated, thereby improving their quality of life.